Vicia ervilia L. seeds newly explored biological activities. Issue 1 (1st January 2017) - Okba, Mona M.; Abdel Jaleel, Gehad A.; Yousif, Miriam F.; El Deeb, Kadriya S.; Soliman, Fathy M.
Abstract: Within the global context of increasing poverty in the developing countries, natural products are important in devising new drugs. Vicia ervilia L. Willd., unlike several fabaceae seeds, is not used for human consumption till now. We aim to discover any possible medicinal use of the seed. Analgesic, anti-inflammatory, antiulcerogenic and antihyperglycemic activities were evaluated using hot plate, carrageenan-induced rat paw edema, ethanol-induced ulcer model and alloxan-induced diabetes methods, respectively. Antiviral activity was evaluated using Methylthiazol Tetrazolium assay. V. ervilia seeds ethanol (70%) extract had significant anti-inflammatory, analgesic, antiulcerogenic, antihyperglycemic and antiviral activities. It is of excellent choice for treatment of several illnesses in developing countries due to its diverse resource, easy accessibility, affordability and its newly proved significant wide range of biological activities.